Central cooperativa de associações: possibilidades e limites para a gestão dos recursos naturais e desenvolvimento local - OLIVEIRA, Sandro Abreu de (Universidade Federal do Pará, 2018)
The dissertation examines a cooperative of associations building in the Marajó Island (Pará State, Amazonia, Brazil) focusing on local development and natural resources management. Particularly, the dissertation tries to understand how a central of cooperative associations contributes to natural resources management and to local development of a município with an economy based on agro-extraction. The dissertation analyses the building process of the Central of Curralinho Agro-extraction, Small-scale, Family-based, Rural producer Cooperative of Association, trying to understand its possibilities and limits in the context of solidarity economy. The theoretical framework involves the debates on natural resources management, solidarity economy and local development. The methodology used was the exploratory case study. The data collection was based on documentary analysis, structured interviews, semi-structured interviews and participant observation. At the end, the study demonstrated that economic-environmental alternatives and the socio-politics relationships built in the scenario which the Central is involved are result of endogenous and exogenous factors. Endogenously, the factors are the credibility of an articulated and compromised leadership and the Central associations’ members’ perception of existence of an historical mild-man and large palm producers’ exploration on small-scale family-based rural producers. Exogenously, the factor is the Central integration with governmental and non-governmental development programs.